Perceptions On Nurses' Preparedness For Flooding Disasters: A Qualitative Study - Purnomo, Edi; Gayatri, Dewi; Setiawan, Agus; Hamid, Achir Yani S (Politeknik Kesehatan Kemenkes Mamuju, 2024)
Preparedness is a series of activities carried out to anticipate disasters through organization and through appropriate and effective measures with the expected result being a significant reduction in the risk and losses caused by disasters. This study aims to explore nurses' perceptions regarding readiness to respond to disasters, nurses' preparedness in facing disasters, the role of nurses in disasters, obstacles and support in providing disaster nursing services. A descriptive qualitative approach was used in this study. Purposive sampling was used to select 10 nurses for focus group discussions and four nurses for in-depth interviews. Data were collected from January to February 2024 and analyzed using content analysis. Readiness to respond to disasters includes two subcategories: disaster experience and reasons to immediately respond to disasters. Health workers' preparedness in facing disasters consists of four subcategories: early warning, collaboration, resources, development of specific training. The role of health workers in disasters consists of two subcategories: preparedness stage and response stage. In addition, obstacles and support in providing disaster services consist of two subcategories: obstacles experienced and support needed in providing nursing services when a disaster occurs. The findings of this study can serve as a basis for developing disaster preparedness enhancement programs for nurses and other health professionals. The results of the study can also be used as important evidence to encourage disaster health service policies in an effort to reduce risks caused by disasters with the involvement of stakeholders.